1996
DOI: 10.1364/ol.21.000450
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved studies of stimulated emission from colloidal dye solutions

Abstract: The temporal profiles of the emission from titania particle suspensions in Rhodamine 640 perchlorate dye solutions excited by 10-ps pulses of 527-nm radiation were measured over a wide range of particle and dye concentrations and laser powers. The dynamics of stimulated emission from random media is modeled by a random walk of photons within the colloid and rate equations for molecular excitations. The pulse width and the dependence of the threshold for laser action on dye and scatter concentration are compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 4 publications
3
36
0
1
Order By: Relevance
“…The real pulse durations might be narrower. In fact, shorter emission pulses of 50 ps or even less were found in other studies devoted to liquid dyes and polymer sheet random lasers following OP excitation [25][26][27]. As it can be seen, the spectral and temporal narrowing of the emission under TP pumping takes place at higher pump densities.…”
Section: Resultssupporting
confidence: 50%
“…The real pulse durations might be narrower. In fact, shorter emission pulses of 50 ps or even less were found in other studies devoted to liquid dyes and polymer sheet random lasers following OP excitation [25][26][27]. As it can be seen, the spectral and temporal narrowing of the emission under TP pumping takes place at higher pump densities.…”
Section: Resultssupporting
confidence: 50%
“…In this framework, it is expected that the number of involved modes increases with the pump energy and, correspondingly, the spectrum widens. However, exactly the opposite happens and this is also accompanied by the shortening of the emitted pulse [24,25,26]. In addition, the fact that strong (or Anderson) localization of light sustains the RL action is still debated.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…After Lawandy et al reported the random laser, many experimental and theoretical studies have been reported. [6][7][8][9] The dependence of spectral and temporal characteristics of the random laser on dye concentration and density of scattering particles have been studied. 6,7 In a high dye concentration sample, bichromatic emission has been observed.…”
Section: Introductionmentioning
confidence: 99%